Long-Term Follow-Up In Paroxysmal Atrial Fibrillation Patients With Documented Isolated Trigger - Palamà, Zefferino; Robles, Antonio Gianluca; Paoletti, Matteo; Nesti, Martina; De Ruvo, Ermenegildo; Scarà, Antonio; Borrelli, Alessio; De Masi De Luca, Gabriele; Rillo, Mariano; Calò, Leonardo; Cavarretta, Elena; Romano, Silvio; et al. (Frontiers in Cardiovascular Medicine, 2023)
Aims. Supraventricular tachycardias may trigger atrial fibrillation (AF). The aim of the study was to evaluate the prevalence of supraventricular tachycardia (SVT) inducibility in patients referred for AF ablation and to evaluate the effects of SVT ablation on AF recurrences.Methods and results. 249 patients (mean age: 54±14 years) referred for paroxysmal AF ablation were studied. In all patients, only AF relapses had been documented in the clinical history. 47 patients (19%; mean age: 42±11 years) had inducible SVT during the electrophysiological study and underwent an ablation targeted only at SVT suppression.Ablation was successful in all 47 patients. The ablative procedures were: 11 slowpathway ablations for atrioventricular nodal re-entrant tachycardia; 6 concealed accessory pathway ablations for atrioventricular re-entrant tachycardia; 17 focal ectopic atrial tachycardia ablations; 13 with only one arrhythmogenic pulmonary vein. No recurrences of SVT were observed during the follow-up (32±18 months). 4 patients (8.5%) showed recurrence of at least one episode of AF.Patients with inducible SVT had less structural heart disease and were younger than those without inducible SVT.A significant proportion of candidates for AF ablation are inducible for an SVT. SVT ablation showed a preventive effect on AF recurrences. Those patients should be selected for simpler ablation procedures tailored only to the triggering arrhythmia suppression.